Kinderhandel oder Koranerziehung?: Kontroversen um die bettelnden Talibé in Senegal - Fuchs, Sarah (transcript, 2020)
Children's rights put to the test: Koranic education as a challenge to the rule of law and Muslim self-understanding in Senegal.